2002
DOI: 10.1523/jneurosci.22-06-02225.2002
|View full text |Cite
|
Sign up to set email alerts
|

Versican Is Upregulated in CNS Injury and Is a Product of Oligodendrocyte Lineage Cells

Abstract: Chondroitin sulfate proteoglycan (CS-PG) expression is increased in response to CNS injury and limits the capacity for axonal regeneration. Previously we have shown that neurocan is one of the CS-PGs that is upregulated (Asher et al., 2000). Here we show that another member of the aggrecan family, versican, is also upregulated in response to CNS injury. Labeling of frozen sections 7 d after a unilateral knife lesion to the cerebral cortex revealed a clear increase in versican immunoreactivity around the lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
170
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 60 publications
8
170
0
Order By: Relevance
“…Previous studies have demonstrated that the CS-PGs produced by OPs-NG2, versican and phosphacan-are inhibitory toward axonal growth (Dou and Levine, 1994;Asher et al, 1999;Fidler et al, 1999;McKeon et al, 1999;Chen et al, 2002;Ughrin et al, 2003): in keeping with these findings, this study showed a greater number of regenerating axons in an environment depleted of NG2 OP cells.…”
Section: Axon Regeneration and Retractionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have demonstrated that the CS-PGs produced by OPs-NG2, versican and phosphacan-are inhibitory toward axonal growth (Dou and Levine, 1994;Asher et al, 1999;Fidler et al, 1999;McKeon et al, 1999;Chen et al, 2002;Ughrin et al, 2003): in keeping with these findings, this study showed a greater number of regenerating axons in an environment depleted of NG2 OP cells.…”
Section: Axon Regeneration and Retractionsupporting
confidence: 89%
“…Various CS-PGs are upregulated in the glial scar (Levine, 1994;Davies et al, 1997;Asher et al, 1999Asher et al, , 2000Fitch et al, 1999;Jones et al, 2002;Tang et al, 2003), and both in vitro and in vivo experiments have demonstrated inhibitory effects of CSPGs on axonal growth (e.g. Snow et al, 1990;McKeon et al, 1991McKeon et al, , 1995Dou and Levine, 1994;Smith-Thomas et al, 1994Fidler et al, 1999;Niederö st et al, 1999;Moon et al, 2001;Bradbury et al, 2002;Chen et al, 2002;Ughrin et al, 2003).…”
mentioning
confidence: 99%
“…This distribution of versican in the white matter has also been described by others, and an axon growthinhibitory role suggested [25]. Furthermore, in vivo investigations have demonstrated an early up-regulation of this CSPG following experimental lesions, the distribution of which was compatible with a regeneration-blocking effect [22,26]. Cells of the oligodendrocytic lineage were reported to be responsible for the post-traumatic up-regulation of versican following spinal lesions.…”
Section: Introductionsupporting
confidence: 76%
“…Like brevican, other brain ECM molecules have also been reported previously to be extractable by glycosidase digestion: hyaluronidase treatment drastically reduces brainspecific hyaluronan-binding protein Bral1 immunoreactivity in cerebellar sections (Oohashi et al 2002), solubilizes neurocan from hippocampal slices (Fö rster et al 2001) and releases versican from pre-oligodendrocytes (Asher et al 2002) indicative of HA-mediated cell surface retention of these molecules. Furthermore, glial hyaluronate binding protein is also released from brain homogenate fractions by enzymatic treatment with chondroitinase ABC (Asher et al 1991).…”
Section: Discussionmentioning
confidence: 97%